Facteurs d’inquiétante étrangeté dans les tableaux vivants de l’art contemporain. L’apport du récit littéraire - Boucher, Mélanie (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2019)
This article considers three central components of tableaux vivants — the transfers of medium that characterize them; their inscription in various disciplines whose codes they partly adopt; and the imperfect immobility they present — that make the expression of the uncanny possible in contemporary art tableaux. Unlike historical and popular tableaux vivants or those related to other disciplines, contemporary art tableaux tend to reproduce not one, but several historical sources and to link them to aspects of personal life. In addition, they tend to exploit different strategies to integrate motion with immobility, which amplifies the effect of the uncanny. This article draws additionally on literary works that feature narratives of tableaux vivants and related practices to investigate the uncanny in contemporary art tableaux.